America Unbound : Encyclopedic Literature and Hemispheric Studies - Barrenechea, Antonio (Book collections on Project MUSE., 2016)
This original contribution to hemispheric American literary studies comprises readings of three important novels from Mexico, Canada, and the United States: Carlos Fuentes's Terra Nostra, Quebecois writer Jacques Poulin's Volkswagen Blues, and Native American writer Leslie Marmon Silko's Almanac of the Dead.